Možnosti ugotavljanja velikosti napake in njene lege v materialu z ultrazvočno difrakcijo - Godec, Boštjan (Kovine zlitine tehnologije, 1997)
Nondestructive testing methods specially ultrasound examination are used to estimate the condition of material as steel construction. Today ultrasonic testing methods are becoming more important as testing equipment enables testing results to be copied out and documented. The ultrasound diffraction method which employs diffracher waves that appear on the sharp edge is presented in the paper. On the basis of the time of flieght as well as known velocity of broadcasting and receiving of ultrasound the position of the top of the crack may be calculated. Laboratory examinations prove that it is possible to determine the precise dimension of cracks and the exact position of defects in material.
Keywords: jeklene konstrukcije; materiali; neporušitvene preiskave; ultrazvočne preiskave; ultrazvočne difrakcije; razpoka